Recent advances in the biodegradation of polyethylene terephthalate with cutinase-like enzymes - Sui, Beibei; Wang, Tao; Fang, Jingxiang; Hou, Zuoxuan; Shu, Ting; Lu, Zhenhua; Liu, Fei; Zhu, Youshuang (Frontiers in Microbiology, 2023)
Polyethylene terephthalate (PET) is a synthetic polymer in the polyester family. It is widely found in objects used daily, including packaging materials (such as bottles and containers), textiles (such as fibres), and even in the automotive and electronics industries. PET is known for its excellent mechanical properties, chemical resistance, and transparency. However, these features (e.g., high hydrophobicity and high molecular weight) also make PET highly resistant to degradation by wild-type microorganisms or physicochemical methods in nature, contributing to the accumulation of plastic waste in the environment. Therefore, accelerated PET recycling is becoming increasingly urgent to address the global environmental problem caused by plastic wastes and prevent plastic pollution. In addition to traditional physical cycling (e.g. pyrolysis, gasification) and chemical cycling (e.g. chemical depolymerization), biodegradation can be used, which involves breaking down organic materials into simpler compounds by microorganisms or PET-degrading enzymes. Lipases and cutinases are the two classes of enzymes that have been studied extensively for this purpose. Biodegradation of PET is an attractive approach for managing PET waste, as it can help reduce environmental pollution and promote a circular economy. During the past few years, great advances have been accomplished in PET biodegradation. In this review, current knowledge on cutinase-like PET hydrolases (such as TfCut2, Cut190, HiC, and LCC) was described in detail, including the structures, ligand‒protein interactions, and rational protein engineering for improved PET-degrading performance. In particular, applications of the engineered catalysts were highlighted, such as improving the PET hydrolytic activity by constructing fusion proteins. The review is expected to provide novel insights for the biodegradation of complex polymers.